Early neuromuscular blocking agents for adults with acute respiratory distress syndrome: a systematic review, meta-analysis and meta-regression - Shuai Shao; Hanyujie Kang; Zhaohui Tong (BMJ Open)
Objective To determine whether neuromuscular blocking agents (NMBAs) can decrease the mortality of patients with acute respiratory distress syndrome (ARDS) and improve their clinical outcomes.Design Systematic review, meta-analysis and meta-regression.Data sources PubMed, Embase, Cochrane Library, Web of Science and ClinicalTrials.gov.Methods Randomised controlled trials (RCTs) comparing the treatment effect of NMBAs with that of placebo (or traditional treatment) in patients with ARDS were carefully selected. The primary outcome was 90-day mortality. The secondary outcomes were 21–28 days mortality, NMBA-related complications (barotrauma, pneumothorax and intensive care unit (ICU)-acquired muscle weakness), days free of ventilation and days not in the ICU by day 28, Medical Research Council score, Acute Physiology and Chronic Health Evaluation II score and arterial oxygen tension (PaO2)/fractional inspired oxygen (FiO2) (at 48 hours and 72 hours). Random-effects meta-regression was used to explore models involving potential moderators. Trial sequential analysis was performed to estimate the cumulative effect on mortality across RCTs.Results NMBAs were not associated with reduced 90-day mortality (risk ratio (RR) 0.85; 95% CI 0.66 to 1.09; p=0.20). However, they decreased the 21–28 days mortality (RR 0.71; 95% CI 0.53 to 0.96; p=0.02) and the rates of pneumothorax (RR 0.46; 95% CI 0.28 to 0.77; p=0.003) and barotrauma (RR 0.56; 95% CI 0.37 to 0.86; p=0.008). In addition, NMBAs increased PaO2/FiO2 at 48 hours (mean difference (MD) 18.91; 95% CI 4.29 to 33.53; p=0.01) and 72 hours (MD 12.27; 95% CI 4.65 to 19.89; p=0.002). Meta-regression revealed an association between sample size (p=0.042) and short-term mortality. Publication year (p=0.050), sedation strategy (p=0.047) and sample size (p=0.046) were independently associated with PaO2/FiO2 at 48 hours.Conclusions In summary, the results suggested that use of NMBAs might reduce 21–28 days mortality, NMBA-related complications and oxygenation. However, NMBAs did not reduce the 90-day mortality of patients with ARDS, which contradicts a previous meta-analysis.PROSPERO registration number CRD42019139440.